Determine the Mean Levels of Vitamin D in Children with First Episode of Urinary Tract Infection - Marium Raza, Nighat Jabeen, Maryam Najam, Rizwana Tareen, Ayesha Intekhab, Qamar Uz Zaman Shahzad, Muhammad Hamza (Pakistan Journal of Medical & Health Sciences, 2022)
Urinary tract infections (UTI) have a prevalence of 1% in boys and about 1-3% in girls. It is more common in boys under 1 year of age after which the incidence is higher in girls. Vitamin D is a fat-soluble vitamin that is synthesized in the skin epithelial cells and also obtained from diet. It has an important role in bone formation and deficiency of vitamin D leads to rickets in children. Objective: To determine the mean levels of vitamin D in children with first episode of urinary tract infection. Study Design: Descriptive cross-sectional study. Place and Duration of Study: Study was conducted at Department of pediatrics, Fauji Foundation Hospital Rawalpindi from 16th Nov, 2021 to 16th May, 2022. Materials and Methods: 50 patients fulfilling the criteria for first episode of urinary tract infection included. All patients age, gender, height and weight were noted. Samples were inoculated on culture media and were examined at 24-48hrs for colony counts and bacterial identification. All patients who were tested positive for urinary tract infection had their serum Vitamin D 25(OH) D3 levels done, a deficiency was defined as values of less than 25ng/ml. Data was entered and analysed in SPSS version 22.0 Results: Mean age (6.70+3.9) with ranges from 02 to 12 years and Mean height (cm) and weight (kg) were (121.76+31.58), (25.64+12.36) respectively. There were 12 (24.0) male and 38 (76.0) female patients who were included in the study according to the inclusion criteria. Mean vitamin-D levels in children with first episode of urinary tract infection in the study was (23.46+1.68). Mean vitamin-D levels in children with first episode of urinary tract infection in children ages 02-06 years was (23.36+1.36), whereas mean vitamin-D levels in children ages 7 – 12 years was (23.54+1.91), Mean vitamin-D levels in among male and female children with first episode of urinary tract infection was (22.83+1.26) ( 23.66+1.76) which was statistically not significant (p-value 0.139). Mean vitamin-D levels in children with first episode of urinary tract infection in children have height between 101 – 175 cm, was (23.50+1.18). Mean vitamin-D levels in children with first episode of urinary tract infection in children having weight between 21 – 50 kg was (23.63+1.88). Conclusion: The study concluded that average vitamin D deficiency was substantial among children with urinary tract infection. Keywords: Urinary tract infections. Vitamin D levels, E coli